Analisis Balanced Scorecard Sebagai Alat Ukur Kinerja pada Unit Simpan Pinjam KUD Sumber Agung Probolinggo - Umi Rahma Dhany (Fakultas Ekonomi Universitas Panca Marga, 2015)
Performance measurement Unit Savings and Loans cooperatives Great Source Pobolinggo only be done with the financial analysis are actually many perspectives that can be analyzed using the Balanced Scorecard method that can be viewed from four perspectives: financial, customer, internal business processes, and learning and growth. Based on the results of data analysis and discussion, it can be concluded that:(1) Based on the measurement of financial performance of cooperatives, concluded enough. It can be seen the current ratio can be considered less. And return on assets (ROA) can be considered good, while the increase in earnings can be considered good. (2) Based on the results of performance measurement is concluded enough customer perspective. This shows that the cooperative has increased customer retention is good. While customer acquisition is considered less. (3) Based on the results of performance measurement, internal business process perspective can be considered good cooperative. (4) Based on the results of performance measurement cooperative learning and growth perspective is concluded either. In 2012 to 2014, Employee Turnover is always 0% in each year. This shows that no employees are out in each year are caused by the presence of employee satisfaction. And in poduktivitas employees increased in every year. While on the capabilities of employees has decreased from 11% to 10% .. This suggests that employees are active in training, or even by the government. (5) Based on unit performance assessment of savings and loans cooperatives Great Source Probolinggo is 4, of the total weight of the standard is 9. So, the average score was 4/9 = 0.44 (located between -1-0). (6) Based on the results of performance assessment shelf unit Borrow Source Supreme KUD overall assessed Less Good / Bad. Keywords: Balanced Scorecard, financial perspective, customer perspective, internal business process and learning and growth perspective, Performance.